2005
DOI: 10.1002/ptr.1766
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical investigation and antioxidant activity ofDuranta repens

Abstract: The ethylacetate fraction of the methanol extract of Duranta repens L. (Verbenaceae) showed radicalscavenging activity in the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Three compounds were isolated from this fraction, i.e. the phenylethanoid glycoside acteoside, the iridoid lamiide and the saponin pseudo-ginsenoside-RT1. Acteoside showed an IC50 of 3.05 +/- 0.09 microg/mL in the DPPH assay, while lamiide and pseudo-ginsenoside-RT1 were not active.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 11 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…The total phenolic contents of Z. spina-christi were measured by the Folin-Ciocalteu assay of Singleton et al [16] and Shahat et al [13] and reported as mgGallic Acid equivalents (GAE) per g of sample. As shown in Figure 2, the total extract, ZSC-1, had the highest phenolic content (82.3 mg/g), followed by ZSC-2, ZSC-3, and ZSC-4 at 76.3, 73.6, and 68.3 mg/g respectively.…”
Section: Total Polyphenolic Contentmentioning
confidence: 99%
“…The total phenolic contents of Z. spina-christi were measured by the Folin-Ciocalteu assay of Singleton et al [16] and Shahat et al [13] and reported as mgGallic Acid equivalents (GAE) per g of sample. As shown in Figure 2, the total extract, ZSC-1, had the highest phenolic content (82.3 mg/g), followed by ZSC-2, ZSC-3, and ZSC-4 at 76.3, 73.6, and 68.3 mg/g respectively.…”
Section: Total Polyphenolic Contentmentioning
confidence: 99%
“…The methanol extract and compounds 1 , 2 and 7 were cytotoxic for HepG2 cells and 7 was the most cytotoxic agent (IC 50 = 1.68, 1.07, 0.94 and 0.60, respectively, Figure 4 ). Although different extracts of D. repens have been investigated as antioxidant and antiviral [ 9 , 10 ], to our knowledge, this work is the first trial to investigate the cytotoxicity of the methanol extract of D. repens leaves against HepG2 solid tumor cell lines. The strong anti-cancer activity of D. repens leaf methanol extract may be attributed to the corresponding activities of the extract constituents.…”
Section: Resultsmentioning
confidence: 99%
“…Thrombin inhibitory coumarins were isolated from fruits [ 8 ]. The ethyl acetate soluble fraction of D. repens methanol extract showed antioxidant and antiviral activities [ 9 , 10 ]. Triterpenes [ 3 ], flavonoids, steroids, C -alkylated flavonoids [ 11 , 8 ], acetosides [ 10 ] and some alkaloids [ 12 ] were isolated from D. repens (var.…”
Section: Introductionmentioning
confidence: 99%
“…cernua [7]. The ethyl acetate fraction of the methanol extract of the whole plant of D. repens showed radical scavenging activity in the 1,1-diphenyl-2-picrylhydrazyl assay [12], antiviral [13], insecticide properties against Aedes aegypti and Attagenus piceus [14], enzyme-inhibitory activity against thrombin [15], and α-glucosidase Inhibitory [16].…”
Section: Introductionmentioning
confidence: 99%